Strawberry fruit skins are far more permeable to osmotic water uptake than to transpirational water loss. - Grecia Hurtado (Public Library of Science (PLoS), 2021)
Water movements through the fruit skin play critical roles in many disorders of strawberry (Fragaria × ananassa Duch.) such as water soaking, cracking and shriveling. The objective was to identify the mechanisms of fruit water loss (dry skin, transpiration) and water uptake (wet skin, osmosis). Fruits were held above dried silica gel or incubated in deionized water. Water movements were quantified gravimetrically. Transpiration and osmotic uptake increased linearly with time. Abrading the thin cuticle (0.62 g m-2) increased rates of transpiration 2.6-fold, the rates of osmotic uptake 7.9-fold. The osmotic potential of the expressed juice was nearly the same for green and for white fruit but decreased in red fruit stages. Fruit turgor was low throughout development, except for green fruit. There was no relationship between the rates of water movement and fruit osmotic potential. The skin permeance for transpiration and for osmotic uptake were both high (relative to other fruit species) but were two orders of magnitude greater for osmotic uptake than for transpiration. Incubating fruit in isotonic solutions of osmolytes of different sizes resulted in increases in fruit mass that depended on the osmolyte. The rate of osmotic uptake decreased asymptotically as molecular size of the osmolyte increased. When transpiration and osmotic uptake experiments were conducted sequentially on the same fruit, the rates of transpiration were higher for fruit previously incubated in water. Fluorescence microscopy revealed considerable microcracking in a fruit previously incubated in water. Our findings indicate that the high permeance for osmotic uptake is accounted for by an extremely thin cuticle and by viscous water flow through microcracks and along polar pathways.